2022
DOI: 10.3390/vaccines10101655
|View full text |Cite
|
Sign up to set email alerts
|

A Comprehensive Review on the Current Vaccines and Their Efficacies to Combat SARS-CoV-2 Variants

Abstract: Since the first case of Coronavirus disease (COVID-19) caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) in 2019, SARS-CoV-2 infection has affected many individuals worldwide. Eventually, some highly infectious mutants—caused by frequent genetic recombination—have been reported for SARS-CoV-2 that can potentially escape from the immune responses and induce long-term immunity, linked with a high mortality rate. In addition, several reports stated that vaccines designed for the SARS-CoV-2 wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 163 publications
0
13
0
Order By: Relevance
“…The primary reason for these small differences appeared to be the level of genetic similarity (homology) between the vaccine antigen and the targeted antibody responses, with the response being more robust when the antigen matches the specific variant. Other studies have also observed strain-specific differential neutralizing responses when comparing the neutralizing capacity induced by Wuhan-Hu-1-specific vaccines with that of variant-adapted vaccine analogs ( 30 , 53 , 56 , 57 ). For example, in Syrian hamsters vaccinated with two IM doses of a multi-antigenic COVID-19 Wuhan-Hu-1-S-specific vaccine candidate based on a synthetic MVA (sMVA) vector or its beta-adapted vaccine analog, it was reported a similar neutralizing activity against the ancestral Wuhan virus in both immunization groups but a higher neutralizing activity against beta and delta variants in hamsters vaccinated with the beta-analog compared with hamsters vaccinated with the COVID-19 Wuhan-Hu-1-specific vaccine candidate ( 30 ).…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…The primary reason for these small differences appeared to be the level of genetic similarity (homology) between the vaccine antigen and the targeted antibody responses, with the response being more robust when the antigen matches the specific variant. Other studies have also observed strain-specific differential neutralizing responses when comparing the neutralizing capacity induced by Wuhan-Hu-1-specific vaccines with that of variant-adapted vaccine analogs ( 30 , 53 , 56 , 57 ). For example, in Syrian hamsters vaccinated with two IM doses of a multi-antigenic COVID-19 Wuhan-Hu-1-S-specific vaccine candidate based on a synthetic MVA (sMVA) vector or its beta-adapted vaccine analog, it was reported a similar neutralizing activity against the ancestral Wuhan virus in both immunization groups but a higher neutralizing activity against beta and delta variants in hamsters vaccinated with the beta-analog compared with hamsters vaccinated with the COVID-19 Wuhan-Hu-1-specific vaccine candidate ( 30 ).…”
Section: Discussionmentioning
confidence: 93%
“…As the virus continues to evolve, there is a need to closely monitor the effectiveness of vaccines against newly emerging VoCs and consider the development of updated or modified vaccines to address any potential antigenic mismatch. The effectiveness of initially approved Wuhan-Hu-1-based COVID-19 vaccines against SARS-CoV-2 variants has been significantly reduced, especially against the Omicron variant ( 53 , 54 ). Nevertheless, different studies have shown that some Wuhan-Hu-1-based COVID-19 vaccines can protect against SARS-CoV-2 VoC morbidity and mortality in different animal models, although with different degrees of infection protection ( 23 32 ).…”
Section: Discussionmentioning
confidence: 99%
“…The neutralizing antibody titer for NVX-CoV2373 peaked between 3.5 and 6 months following vaccination and was higher than Ad26.COV2.S but equivalent to the mRNA vaccines, BNT162b2 and mRNA-1273 [ 92 ]. Although none are currently in use, more than 60% of vaccines being studied use the protein subunit technique [ 114 ]. The most frequent adverse effects of NVX-CoV2373, which last for two to three days, are headache, weariness, and malaise.…”
Section: Vaccinementioning
confidence: 99%
“…Contrarily, patients with COVID-19 who were severely infected experienced an excessive release of cytokines and chemokines, such as interleukin (IL)-1, IL-2, IL-6, IL-7, IL-8, IL-10, granulocyte-colony stimulating factor (GCSF), and tumour necrosis factor-alpha (TNF-α) [ 34 , 35 , 36 , 37 ]. Notably, it has been suggested that the abnormally high levels of circulating cytokines in severe COVID-19 patients have a detrimental effect on T-cell survival and/or multiplication [ 38 , 39 , 40 , 41 , 42 ]. Post-mortem investigations of COVID-19 patients revealed considerable lymphocyte mortality in lymph follicles and paracortical regions of lymph nodes, which may have been caused, among other things, by macrophage-derived IL-6 that directly promoted lymphocyte necrosis [ 35 , 43 , 44 ].…”
Section: T Cells Response and Cytokine Stormmentioning
confidence: 99%